Effect of mach number on wall pressure flow field for area ratio 2.56 - Ashfaq, Syed; Khan, Sher Afghan (International Organozation of Scientific Research (IOSR) Journals, 2014)
This paper presents the experimental results on the flow characteristics of a suddenly expanded flow from the convergent nozzle for subsonic flow. In the present study micro jets were used to investigate the effect of micro jets on wall pressure flow field in the enlarged duct. Accordingly an active control in the form of four micro jets of 1 mm orifice diameter located at 900 intervals along a pitch circle diameter of 1.3 times the nozzle exit diameter in the base region was employed. The Mach numbers of the present studies were M = 0.9, 0.8, and 0.6 and the area ratio (ratio of area of suddenly expanded duct to nozzle exit area) studied was 2.56. The length-to-diameter (i.e. L/D) ratio of the sudden expansion duct was varied from 10 to 1. From the results, it is seen that the flow in the base region is dominated by the waves, the general perception what we have that correctly expanded flow will be from waves is proved to be wrong; also, it is found that for L/D in the range L/D = 10 and 8 the flow remains oscillatory mostly for all the Mach numbers. However, these oscillations are suppressed gradually either with the increase in the L/D ratio in the range 3 to 6 or with decrease in the level of inertia level. The present study explicitly reveals that, the wall pressure in a suddenly expanded axi-symmetric duct can be controlled by employing micro jets. Since the flow field in the enlarged duct remained undisturbed hence, we can say that the control in the form of micro jets don’t disturb the field.